Experimental investigation on spray characteristics of agricultural full-cone pressure swirl nozzle - Xue, Xiuyun; Xu, Xufeng; Lyu, Shilei; Song, Shuran; Ai, Xin; Li, Nengchao; Yang, Zhenyu; Li, Zhen (International Journal of Agricultural and Biological Engineering, 2023)
The spray characteristics of a full-cone pressure swirl nozzle have been investigated in this study. The results were defined by Reynolds number, which focuses on the breakup of liquid film, droplet size, velocity, and liquid volume flux under different Reynolds numbers at the near-field spray. The spray structure was visualized using a high-speed camera, and the characteristics of droplets were measured using a Phase Doppler Anemometer (PDA) in both the radial and axial directions. The tests were carried out at varying spray pressures (0.2 to 1.0 MPa), corresponding to different Reynolds numbers (5369 to 12006). It was found that when the Reynolds number rises, the liquid became more unstable after leaving the nozzle, causing the liquid film to break up faster. According to the measurements of PDA, the coalescence of droplets increased due to the centrifugal effect. What’s more, the velocity of the droplets fluctuates significantly in the radial direction, and the droplets with a smaller particle size had a higher average velocity. From the perspective of liquid distribution, the increase in Reynolds number caused the spray liquid to move in the radial direction gradually. In contrast, the liquid volume distribution changed in the radial direction more obviously than in the axial direction, growing to the maximum along the radial direction and gradually reducing. It can provide a reference for selecting operating parameters for actual agricultural spray operations and the design of electrostatic nozzles through the research on breakup and droplet characteristics. Keywords: full-cone pressure swirl nozzle, droplet size, droplet velocity, liquid volume flux, high-speed camera, PDA DOI: 10.25165/j.ijabe.20231604.7088 Citation: Xue X Y, Xu X F, Lyu S L, Song S R, Ai X, Li N C, et al. Experimental investigation on spray characteristics of agricultural full-cone pressure swirl nozzle. Int J Agric & Biol Eng, 2023; 16(4): 29–40.